2017
DOI: 10.18805/lr.v40i04.9004
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical basis of genotypic and bio-agent induced stem rot resistance in groundnut

Abstract: Stem rot (Sclerotium rolfsii Sacc.) resistance in groundnut genotypes was due to activities of defense enzymes such as, catalase, peroxidase and polyphenol oxidase. Bio-agent, Bacillus amyloliquefaciens isolated from groundnut rhizosphere enhances the activities of defense enzymes through salicylic acid induced systemic resistance. In resistant genotypes (NRCGCS-19 and NRCGCS-319) higher activities of defense enzymes were recorded constitutively while in susceptible genotypes it was increased after bio-agent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Song et al (2013) also reported that lipopeptides produced by B. amyloliquefaciens anti-CA (Candida albicans) limit fungal growth of C. albicans. Bacillus amyloliquefaciens isolated from groundnut rhizosphere enhances the activities of defense enzymes through salicylic acid induced systemic resistance and several enzymes such as chitinase, peroxidase, catalase and polyphenol oxidase have strong negative correlation with disease severity index (Rajyaguru et al, 2017). Two antagonistic bacterial strains of Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Song et al (2013) also reported that lipopeptides produced by B. amyloliquefaciens anti-CA (Candida albicans) limit fungal growth of C. albicans. Bacillus amyloliquefaciens isolated from groundnut rhizosphere enhances the activities of defense enzymes through salicylic acid induced systemic resistance and several enzymes such as chitinase, peroxidase, catalase and polyphenol oxidase have strong negative correlation with disease severity index (Rajyaguru et al, 2017). Two antagonistic bacterial strains of Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Salicylic acid induced systemic resistance to enhance the activity of the defense enzymes. Enzymes catalase, peroxidase, polyphenol oxidase and chitinase showed strong negative correlation with disease severity index [ 37 ]. Therefore, we use bio-pesticides to improve the enzyme activity of crops to reduce the severity of crop diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the OD values for Polyphenol oxidase enzyme assay were measured by taking 2900 µl of 0.1 M catechol in the 10 mM phosphate buffer of pH 6.0, 100 µl milli-Q and enzyme supernatant in the quartz cuvette at 490 nm for one min, at intervals of 15 s in the spectrophotometer. The OD value for a similarly treated control sample (blank without enzyme supernatant) was deducted from test readings [ 27 ].…”
Section: Methodsmentioning
confidence: 99%